2008
DOI: 10.1099/mic.0.2008/019380-0
|View full text |Cite
|
Sign up to set email alerts
|

Mucins in the host defence against Naegleria fowleri and mucinolytic activity as a possible means of evasion

Abstract: Naegleria fowleri is the aetiological agent of primary amoebic meningoencephalitis (PAM). This parasite invades its host by penetrating the olfactory mucosa. During the initial stages of infection, the host response is initiated by the secretion of mucus that traps the trophozoites. Despite this response, some trophozoites are able to reach, adhere to and penetrate the epithelium. In the present work, we evaluated the effect of mucins on amoebic adherence and cytotoxicity to Madin-Darby canine kidney (MDCK) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…In the mucin-producing cell line NCI-H292, N. fowleri induced the release of reactive oxygen species, which led to the activation of epidermal growth factor receptor, which in turn stimulated production of the mucin MUC5A and IL-8 secretion (314). Despite this host response, by 12 h, N. fowleri was observed adhering to and invading the olfactory epithelium in mice, suggesting that the amoeba may have pathogenic mechanisms to efficiently penetrate the mucous layer (392). In vitro, it was shown that both live trophozoites and crude total N. fowleri extracts demonstrated mucinolytic activity.…”
Section: Protozoamentioning
confidence: 96%
See 2 more Smart Citations
“…In the mucin-producing cell line NCI-H292, N. fowleri induced the release of reactive oxygen species, which led to the activation of epidermal growth factor receptor, which in turn stimulated production of the mucin MUC5A and IL-8 secretion (314). Despite this host response, by 12 h, N. fowleri was observed adhering to and invading the olfactory epithelium in mice, suggesting that the amoeba may have pathogenic mechanisms to efficiently penetrate the mucous layer (392). In vitro, it was shown that both live trophozoites and crude total N. fowleri extracts demonstrated mucinolytic activity.…”
Section: Protozoamentioning
confidence: 96%
“…In vivo studies have shown that N. fowleri induces mucus production within the nasal cavity as early as 1 h postinfection and that, by 6 h, amoebae are covered by mucus and surrounded by neutrophils (392). In the mucin-producing cell line NCI-H292, N. fowleri induced the release of reactive oxygen species, which led to the activation of epidermal growth factor receptor, which in turn stimulated production of the mucin MUC5A and IL-8 secretion (314).…”
Section: Protozoamentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of infection, N. fowleri trophozoites are embedded in a large amount of mucus and surrounded by an inflammatory infiltrate composed mainly of neutrophils (Cervantes-Sandoval et al, 2008a;RojasHernández et al, 2004). However, N. fowleri is able to degrade the mucus by secreting a 37 kDa cysteine protease (Cervantes-Sandoval et al, 2008b), which most likely allows the amoeba to evade the mucus and adhere to the olfactory epithelium (Cervantes-Sandoval et al, 2008a). For many micro-organisms, adherence is one of the most important features observed during the early invasion of different tissues or organs (Kucknoor et al, 2005;McCoy et al, 1994;Panjwani, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of the early events of infection using a murine model have shown that the amoebae induce intense mucus secretion and an inflammatory reaction in the nasal cavity (Cervantes-Sandoval et al, 2008a;Rojas-Hernández et al, 2004). However, N. fowleri is able to evade host innate defence mechanisms by mucous degradation that occurs via a 37 kDa cysteine protease (Cervantes-Sandoval et al, 2008b), allowing the amoebae to adhere to the neuroolfactory epithelium. A striking observation is that N. fowleri transits the epithelium (Cervantes-Sandoval et al, 2008a;Rojas-Hernández et al, 2004) by traversing cell junctions without causing any apparent damage.…”
Section: Introductionmentioning
confidence: 99%